PENERAPAN MODEL VAR DALAM PENGUKURAN RISIKO PENURUNAN OPERATIONAL REVENUE PADA INDUSTRI TELEKOMUNIKASI - Giriningtyas Dina Theresia; Ruli Satya Dharma; Batara Maju Simatupang (STIE Indonesia Banking School, 2015)
The objective of this paper is to measure operational risk in the telecommunications company using Value at Risk (VAR) model. VaR methods used in this paper are historical simulation and variance-covariance approach. The results of this paper indicated that the average value of historical simulation is smaller than variance covariance. Both methods show valid results when tested using backtesting methods. This result shows that both methods can be used to calculate the amount of risk reduction in operational revenue.